Elements concentrations in the scalp hair of methamphetamine abusers. (April 2015) - Luo, Ruxin; Zhang, Sujing; Xiang, Ping; Shen, Baohua; Zhuo, Xianyi; Ma, Dong
Highlights: Elements contents in the hair of METH abusers and control subjects were determined. Differences in the contents of elements were observed. Both essential and toxic elements were included. Abstract: The concentrations of 16 elements (As, Au, Ca, Cd, Co, Cr, Cu, Fe, Hg, Mg, Mn, Mo, Ni, Se, Sr and Zn) in the hair of 40 methamphetamine (METH) abusers and control subjects were determined by inductively coupled plasma mass spectrometry (ICP-MS). Comparisons of the element levels in the hair of properly matched METH abuser and control groups revealed significant imbalances in the concentrations of 6 elements (As, Au, Ca, Cu, Mg and Sr) between the abuser and control groups. Ca ( p  < 0.01), Cu ( p  < 0.05), Mg ( p  < 0.01) and Sr ( p  < 0.01) levels are significantly lower in the hair samples of METH abusers compared to control subjects, whereas the As ( p  < 0.01) and Au ( p  < 0.01) concentrations are higher. The concentration of the remaining elements in the hair of METH abusers was similar to the concentration in the control subjects. The geometric means for each element in hair of METH abuser and control subjects are presented. The cause of these alterations is also discussed.